(untitled) (Limes: Revista de Estudios Clásicos, 2023)
The s. V of Pericles and s. XX have been envolved in protracted wars. The former has maintained defining warlike confrontations against the Persians and between Sparta and Athens; the last century has seen the two world wars that represented the most drastic rupture in all of history. We analyze two literary manifestations that make the war problem visible in a dialogue that seems to obviate the distance of the centuries. Aeschylus’ Persae written at Hiero’s court of Syracuse (472 B.C.) is the first preserved Greek tragedy, and it deals with the defeat suffered by the Persians in Greece, when they faced each other in the battle of Salamis, which changed the course of history. In the 20th century, Wilfred Owen’s poem “Dulce et decorum est” makes the reader feels part of the march of defeated men coming back from the war. Other poems also describe the soldiers’ painful bodies remains. Both manifestations propose to study the phenomena and processes whose genesis has become independent because they belong to different civilizations (…) collected and brought together for study and justified to the extent that common sociohistorical conditions are implied (cf. Guillén 1993: 71). We follow Kate McLoughlin´s position on literary war representations. In her study Authoring war. The literary representation of war from the Iliad to Iraq (2011: 15), she stated that “there is a common ground between conflicts separated by thousands of years implying that in writing war “the past is altered by the present as much as the present is altered by the past”. Focusing on Aeschylus and Owen we ask ourselves if he can state that there is or not a common expression or realization of collective human subjectivity when writing war experiences.